Unconventional Gas and the European Union: Prospects and Challenges for Competitiveness - Herman R. J. Vollebergh; Eric Drissen (Center for Economic Studies and ifo Institute (CESifo), 2014)
This article studies the likely impact of unconventional gas developments in the U.S. on EU competitiveness. We find, first of all, little evidence for a prosperous unconventional gas development in Europe. Second, the U.S. boom has already a strong impact on both world and European energy markets. In particular, lower U.S. gas and coal prices have changed relative energy prices both at home and abroad. Finally, competitiveness impacts in some (sub)sectors will be considerable. These impacts are not only related to production based on gas use as a feedstock but also on the byproducts' from unconventional gas production, such as ethylene, propane and butane. However, several indirect impacts, such as lower coal import prices, may soften the adverse competitiveness impact in the EU.
Keywords: L71; O52; Q31; Q41; Q43; 330; shale gas; hydrocarbon resources; energy demand and supply; non-renewable resources; competitiveness impacts; European Union